The role of Growth arrest-specific 6 in Notophthalmus viridescens forelimb regeneration - Beug, Shawn (University of Ottawa (Canada), 2004)
Red-spotted newts are capable of regenerating diverse structures and organs, including limb, tail and retina. The epimorphic regenerative response is a complex process that involves dedifferentiation, cellular proliferation and transdifferentiation. Although receptor tyrosine kinases (RTKs) and their ligands are important for normal cellular physiology, no studies have as of yet attempted to isolate and characterize any of these receptors and their ligands during newt forelimb regeneration. I isolated a newt homologue of growth arrest-specific 6 (NvGas6), a RTK ligand involved in multiple functions during ontogeny and normal physiological processes, and its expression was characterized in a polyclonal blastema cell line (B1H1) and during limb regeneration. NvGas6 encodes for a 671 amino acid polypeptide that shares 64% identity (78% similarity) with mammalian Gas6. In B1H1 cells, NvGas6 is upregulated during myogenesis and is downregulated during cell cycle reentry. Upon amputation, NvGas6 expression increases, peaking during maximal blastemal cell proliferation and declines during redifferentiation. NvGas6 transcripts were colocalized to distal mesenchymal cells during dedifferentiation and proliferation, and were found in areas of redifferentiation. Although the in vitro and in vivo results seem paradoxical, studies by others have shown that Gas6 can have diverse roles in cell survival, proliferation and differentiation, it is possible that NvGas6 is involved in cell survival in vitro and cellular proliferation in vivo. However, taken together, these results suggest that NvGas6 may be primarily involved in mediating cell survival and migration during regeneration.
Keywords: Biology, Molecular.